2019
DOI: 10.1155/2019/2910278
|View full text |Cite
|
Sign up to set email alerts
|

Protium javanicum Burm. Methanol Extract Attenuates LPS-Induced Inflammatory Activities in Macrophage-Like RAW264.7 Cells

Abstract: Protium javanicum Burm. f. is a medicinal plant used in traditional medicine. Gum and oleoresins from this plant have been used as anti-inflammatory agents for treating ulcers, headaches, eyelid inflammation, and rheumatic pain. However, its anti-inflammatory mechanism of action is still unknown. To better understand the mechanism, we used lipopolysaccharide- (LPS-) treated RAW264.7 cells to measure inflammatory mediators with the Griess assay and to identify target signaling molecules by immunoblot analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
0
8
0
2
Order By: Relevance
“…However, proinflammatory induction and stress conditions lead to chronic diseases [ 53 ]. Macrophages are responsible for secreting inflammatory cytokines after activation and mediating inflammation [ 54 ]. Lipopolysaccharide (LPS) is a part of Gram-negative bacteria's outer wall that activates macrophages and leads to the release of specific proinflammatory cytokines such as promoting tissue damage and chronic diseases [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, proinflammatory induction and stress conditions lead to chronic diseases [ 53 ]. Macrophages are responsible for secreting inflammatory cytokines after activation and mediating inflammation [ 54 ]. Lipopolysaccharide (LPS) is a part of Gram-negative bacteria's outer wall that activates macrophages and leads to the release of specific proinflammatory cytokines such as promoting tissue damage and chronic diseases [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…LPS can stimulate the acute inflammatory response by increasing expression of tumor necrosis factor (TNF-α) and interleukin 6 (IL-6), inducible nitric oxide synthase (iNOS), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), and cyclooxygenase-2 (COX-2), successively (Ahujaa et al, 2019). In the process, the expressions of TNF-α, IL-6, iNOS/NO, NF-κB, as well as COX-2 will be upregulated, which will promote tissue damage and chronic disease.…”
Section: Identification Of New Compoundsmentioning
confidence: 99%
“…ese results suggest that Tt-ME selectively inhibited LPS-induced inflammatory signaling in RAW2647 macrophages. Our recent findings reported that Syk and Src contribute to NF-κB-mediated phosphorylation of IκBα at early time points [38,49,50]. Meanwhile, MEK1/2, MKK3/6, TAK1, and IRAK1 are known to be the upstream molecules of ERK, JNK, and p38 [51][52][53].…”
mentioning
confidence: 96%